The characteristics of a test liquid formulation for use in evaluating the performance of handling and metering systems - Antuniassi, Ulisses Rocha [UNESP]; Miller, PCH (British Crop Protection Council, 1998)
Injection metering systems are an important option for the development of pesticide application equipment, with advantages relating to minimising the need for disposal of unused pesticide, improving the ease of cleaning and optimising the accuracy of chemical application. For all injection systems, characteristics such as the steady-state accuracy of delivered dose, dose stability and the time response for dose step changes are related to the ability of the system to operate with different chemical formulations. A system designed to inject liquids should be able to accommodate changes in viscosity and density. The aim of this study was to develop a methodology for testing chemical injection systems using liquids with different viscosities. The experimental arrangement simulating applications with injection metering systems used dye and salt solutions as tracers. Tests were conducted to analyse the influence of salt on the characteristics of the water and a viscous solution. Results showed that the salt interfered with the dye stability in the water solution. In tests with a viscous test liquid, the salt was introduced at different steps during the mixing process, providing four different liquids to be analysed in terms of viscosity, density and pH. Some differences in liquid characteristics were found which could influence the performance of the injection systems.